The effect of seed thickness alignment on the uniformity of planting materia - Golev Alexandеr; Goleva Galina; Ivannikov Valery; Buchtoyarov Vladimir (BIO Web of Conferences)
The results of studies on the effect of calibration of Scots pine (Pinus sylvestris) seeds by size (thickness) on the yield of standard seedlings are presented in order to assess the effect of the lattice-free technology of calibration of scots pine seeds on the yield of standard seedlings when growing them in a nursery. The seed batch of scots pine before sowing was calibrated on an experimental sample of a lattice-free separator in size (thickness). The size gap in the fractions was determined experimentally using end measures and an electronic caliper, based on the minimum and maximum sizes (thickness) of the seeds. As a result, two fractions of seeds were obtained. The resulting seed fractions were sown on nursery areas. Uncalibrated seeds were used as a control. It was found that the highest yield of standard seedlings (94-98%) was observed when using calibrated seeds regardless of the fraction. When sowing with uncalibrated seeds, the yield of standard seedlings was only 64-79%. The height of seedlings grown from uncalibrated seeds varied from 5 to 32 cm, calibrated (large fraction) – from 13 to 23 cm, calibrated (small fraction) – 10 to 13 cm. The diameter of the root neck in crops with uncalibrated seeds varied from 1.86 mm to 11.94 mm, calibrated large seeds – from 3.88 to 4.56 mm, calibrated small seeds – from 2.99 to 3.41 mm.